Korean Wave and Social Changes in Language and Discourse in Indonesia - Sonezza Ladyanna (Universitas Andalas, 2023)
Generally, research on social change in Southeast Asian countries shows that large-scale social changes occurred as a result of colonialism, including the end of the colonial period, state formation, and ideological changes. However, in this article, I will explain how social change occurred after the major changes associated with the end of the colonial period, named after the media developed rapidly connecting pop cultures from one nation to another, such as the Korean Wave, which was massively transferred to Indonesia by the media post-2000s. Korea, as one of the developed countries that have no colonial history with Indonesia and other Southeast Asian countries in Asia, brings a new color of social change to Indonesia through the Korean Wave, which was previously heavily influenced by the West.